PENILAIAN AUTENTIK (AUTHENTHIC ASSESSMENT) PADA KETERAMPILAN PROSES MAHASISWA PADA PERKULIAHAN TEKNIK DAN MANAJEMEN LABORATORIUM (TML) DI PROGRAM STUDI PENDIDIKAN BIOLOGI FKIP UNIVERSITAS RIAU - Yuslim Fauziah, '; Arnentis ' '; Nur Chalida Sari (Program Studi Pendidikan Biologi, 2014)
Descriptive research has been conducted to determine the skills of the at the courseTechnique and Management of Laboratory based authentic assessment (AuthenthicAssessment). This study was conducted from September to December 2013. Subjectswere students of the 1st semester of the academic year 2013/2014, amounting to 54people consisting of 7 men and 47 woman. Parameters measured were indicators ofprocess skills of students with the skills of observation, classification, communication,inference, predicting, formulating hypotheses, and interpretation of data. The averagepercentage of process skill of the student in the course Technique and Management ofLaboratory is 83.24 (excellent category). Percentage of observation skills are 85.31(excellent category), skill classification is 83.30 (excellent category), communicationskills are 79.80 (good categories), is 79.22 inference skills (good categories), theprediction skill is 88.29 (excellent category), skills to formulate hypotheses was 86.07(excellent category), and interpretation skills are 80.83 (both categories). Processskills of students in Technique and Management of Laboratory based authenthicassessment (Assessment Authenthic) academic year 2013/2014 are in excellentcategory.Keywords: process skills, technique and management of laboratory, assessmentauthenthic